The Relationship between Social Media Addiction and Mental Health in Grade XII Students of SMA N 1 Kawangkoan - Priscila Evangelin Asa; Sri Rejeki Monica Suparlan; Yesmin Tuwohingide (International Journal of Health and Medicine, 2025)
Objective:This study aimed to determine the relationship between Social Media addiction and Mental Health among grade XII SMA N 1 Kawangkoan students. Methods: This study used a descriptive design.cross sectional study was conducted in September 2024 at SMA N 1 Kawangkoan. The sample size was 75. Data analysis was performed using the Spearman’s rank test. Results: There was a very weak relationship between social media addiction and mental health (correlation coefficient = -0.241 and Sig. 2-tailed = 0.037 <0.05) and not in the same direction, indicating that the higher the social media addiction, the lower the mental health. Conclusion: There is a weak and inverse relationship between social media addiction and mental health in grade XII students of SMA N 1 Kawangkoan. It is recommended that schools provide education to students about the impact of excessive use of social media on adolescent mental health and how to prevent social media addiction.